1994
DOI: 10.1111/j.1600-0684.1994.tb00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of inactivated whole HIV‐2 vaccines with various adjuvants in cynomolgus monkeys

Abstract: Twenty-one cynomolgus monkeys were immunized with whole inactivated HIV-2 preparations administered with various adjuvants (incomplete Freund's adjuvant, Alum, Ribi, MDP, or Iscoms) and challenged with 10 or 100 MID50 of a homologous monkey-cell grown, cell-free HIV-2. Seven animals were completely protected against infection, three showed reduced virus replication. The vaccines elicited neutralizing and ADCC antibodies; the titers did not correlate with protection. Immunization with a whole inactivated vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In a vaccination experiment by Lehner et al (1996) protection against infectious challenge with SIVmac of macaques was associated with significantly increased levels of CD8 suppressor factor and the β-chemokines RANTES and MIP-1β. In our previous vaccine experiments using whole inactivated HIV-2 (Putkonen et al, 1994), native HIV-2 gp125 (Nilsson et al, 1995) or recombinant HIV-2-canarypox virus (Andersson et al, 1996) we have shown complete protection against challenge with infectious HIV-2 in 30-50 % of the animals. The protective efficacy of the vaccines was correlated neither to humoral immunity as determined by titres of binding antibodies, neutralizing antibodies and antibodies active in antibody-dependent cellular cytotoxicity nor to cellular immunity as determined by the presence of HIV-2-specific T-cell proliferative responses and cytotoxic Tlymphocytes.…”
Section: Simian Immunodeficiency Virus (Siv) Uses the Ccr5 Chemokine mentioning
confidence: 79%
See 1 more Smart Citation
“…In a vaccination experiment by Lehner et al (1996) protection against infectious challenge with SIVmac of macaques was associated with significantly increased levels of CD8 suppressor factor and the β-chemokines RANTES and MIP-1β. In our previous vaccine experiments using whole inactivated HIV-2 (Putkonen et al, 1994), native HIV-2 gp125 (Nilsson et al, 1995) or recombinant HIV-2-canarypox virus (Andersson et al, 1996) we have shown complete protection against challenge with infectious HIV-2 in 30-50 % of the animals. The protective efficacy of the vaccines was correlated neither to humoral immunity as determined by titres of binding antibodies, neutralizing antibodies and antibodies active in antibody-dependent cellular cytotoxicity nor to cellular immunity as determined by the presence of HIV-2-specific T-cell proliferative responses and cytotoxic Tlymphocytes.…”
Section: Simian Immunodeficiency Virus (Siv) Uses the Ccr5 Chemokine mentioning
confidence: 79%
“…Furthermore among more than 150 monkeys tested we have not seen any naive animal being protected from an infectious challenge with HIV-2 or SIV given intravenously or intrarectally (Andersson et al, 1996 ;Nilsson et al, 1995 ;Putkonen et al, 1994 ;our unpublished observations). In these experiments 10 MID &!…”
Section: Simian Immunodeficiency Virus (Siv) Uses the Ccr5 Chemokine mentioning
confidence: 99%
“…Using experimental vaccines in monkey models, several investigators demonstrated the correlation of increased chemokine levels with protection from lentivirus infections (1,16,23). RANTES, MIP-1␣, and MIP-1␤ were also shown to selectively inhibit cell fusion mediated by HIV-1 envelope glycoproteins (2).…”
Section: Discussionmentioning
confidence: 99%
“…Target cells were prepared by incubation for 16 h at 37ЊC in a 5% CO 2 atmosphere with both recombinant vaccinia virus expressing SIVmac gag or env or the irrelevant equine herpesvirus 1 gH gene and 0.5 mCi of Na 2 51 CrO 4 (ICN, Irvine, Calif.) per ml. Effector cells were incubated with 51 Crlabeled target cells for 5 h with effector-to-target cell ratios of 20:1, 10:1, 5:1, and 3:1. Specific release was calculated as [(experimental release Ϫ spontaneous release)/(100% release Ϫ spontaneous release)] ϫ 100.…”
Section: Methodsmentioning
confidence: 99%